Perspective Discordance in Goals-of-Care Discussions and Palliative Care Among Patients, Families, and Clinicians in Adult Intensive Care Units: A Scoping Review - Rifkal Artha Yuda; Riska Cahyani Zahra; Rezki Ramadhani (Universitas Airlangga, 2026)
Introduction: Goal-of-care discussions in the Intensive Care Unit (ICU) involve patients, families, and healthcare professionals who may hold different perspectives on prognosis, treatment priorities, and care expectations. These differences can influence communication, shared decision-making, and palliative care. However, evidence on perspective discordance in adult ICU settings has not been comprehensively mapped. This scoping review aimed to identify and map the existing literature on perspective discordance in goal-of-care discussions and palliative care in adult ICUs. Method: This scoping review followed the Arksey and O'Malley framework and the PRISMA-ScR guidelines. Literature searches were conducted in PubMed, Scopus, EBSCOhost, and Taylor & Francis for English-language studies published between 2021 and 2026. Study selection was guided by the Population–Concept–Context (PCC) framework. Results: Of 785 records identified, 22 full-text articles were assessed for eligibility, and nine studies were included in the final synthesis. The included studies reported prognostic discordance, differences in perceptions of quality of life and patient dignity, and disagreements regarding life-sustaining treatment. Communication barriers and challenges in shared decision-making were also frequently identified. Several studies highlighted the value of structured family meetings and communication-focused interventions to support discussions between families and healthcare professionals. Conclusions: The literature indicates that perspective differences in ICU goal-of-care discussions are primarily related to communication processes, shared decision-making, and palliative care discussions. Prognostic discordance and differences in treatment expectations were the most commonly reported forms of perspective differences. These findings highlight the need to strengthen structured communication strategies and promote earlier integration of palliative care to facilitate shared decision-making and align treatment goals among patients, families, and clinicians in adult ICUs.